Early weaning impairs body composition in male mice - Maria Carolina Borges; Marcelo Macedo Rogero; Ivanir Santana de Oliveira Pires; Primavera Borelli; Julio Tirapegui (Universidade de São Paulo, 2009)
This study aimed to evaluate the effect of early weaning on body composition and on parameters related to nutritional status in mice. The experimental group consisted of male Swiss Webster mice that were weaned early (at postnatal day fourteen) and fed an appropriate diet for growing rodents until postnatal day twenty-one (EW group). The control group consisted of male mice breastfed until postnatal day twenty-one (CON group). All animals were sacrificed on the twenty-first day of life. The EW group showed a decrease in liver and muscle protein content and concentration, brain protein concentration, brain DNA content and concentration, as well as liver and muscle protein/RNA ratio (p<0.05). Concerning body composition, the EW mice showed increased moisture content, increased moisture and lipid percentage, and a smaller percentage and content of protein and ash in the carcass (p<0.05). These results indicate that early weaning impairs body composition and parameters related to nutritional status, which may be explained by retarded chemical maturation processes. This data may contribute to the overall understanding of the influence of breastfeeding versus feeding with artificial milk on body composition and on nutritional status. O presente estudo objetivou avaliar o efeito do desmame precoce sobre a composição corporal e sobre parâmetros indicativos do estado nutricional de camundongos. O grupo experimental consistiu de camundongos Swiss Webster, machos, desmamados precocemente (14º dia de vida) e alimentados com ração apropriada para roedores em crescimento até o 21º dia pós-natal (grupo DESM). O grupo controle consistiu de camundongos amamentados até o 21º dia pós-natal (grupo CON). Todos os animais foram sacrificados no 21º dia de vida. O grupo DESM apresentou redução da concentração e conteúdo hepático e muscular de proteínas, da concentração cerebral de proteínas, da concentração e conteúdo cerebral de DNA e da razão proteína/RNA hepática e muscular (p<0,05). Quanto à composição corporal, o grupo DESM apresentou maior conteúdo de umidade, maior percentual de umidade e lipídios e menor conteúdo e percentual de cinzas e proteína na carcaça (p<0,05). Os resultados indicam que o desmame precoce acarreta em prejuízo à composição corporal e a parâmetros indicativos do estado nutricional, o que pode estar relacionado ao retardo do processo de maturação química. Os dados do presente estudo podem contribuir para o entendimento da influência da alimentação com fórmulas infantis sobre a composição corporal e sobre o estado nutricional.